EFEK MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW MENGGUNAKAN PETA KONSEP TERHADAP HASIL BELAJAR SAINS SISWA KELAS V SD NEGERI 101777 SAENTIS - Apriana Apriana; Mara Bangun Harahap; Nurdin Bukit (JURNAL TEMATIK, 2019)
This study aims to determine the effect of the jigsaw type cooperative learning model using concept maps on students' learning outcomes in sub-themes of housing objects rather than direct learning models. This type of research is quasi-experimental. The results showed that the jigsaw cooperative learning model using concept maps gave a higher influence on student science learning outcomes compared to the direct learning model with tcount = 4.351 and p = 0,000. The results of the analysis obtained science learning outcomes of students taught with a high-category jigsaw model with a mean gain score of 0.73 with a standard deviation of 0.099 and declared normal distribution (p = 0.581). Student science learning outcomes taught with direct learning models are classified into the medium category with an average gain score of 0.61 with a standard deviation of 0.122 and stated as normal distribution (p = 0.581). The two sample groups were stated to be from a homogeneous population with a value of p = 0.714, the cognitive domain of the experimental class students who developed after being taught the jigsaw type cooperative learning model using concept maps was C1 at 77.5% (high); C2 of 72.4% (high); C3 of 71.3% (high); C4 is 72.1% (high). Abstrak: Penelitian ini bertujuan untuk mengetahui peng